Acute Brucella infection associated with splenic infarction: a case report and review of the literature - Shi, Limei; Wang, Shuang; Li, Xiaohua; Li, Xin; Li, Yuxiang; Wang, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Brucella infection often involves multiple organ systems with non-specific clinical manifestations, and cutaneous involvement is uncommon. Splenic infarction and leukocytoclastic vasculitis also rarely occur together in the course of brucellosis infection. We report the case of a 47-year-old man with Brucella combined with splenic infarction. The patient presented with fever; large liver, spleen, and lymph nodes; muscle and joint pain; positive laboratory tests for blood cultures (Brucella abortus); and imaging suggestive of splenic infarction. After treatment with streptomycin, doxycycline, and rifampicin, the patient’s clinical symptoms and splenic damage improved. Detailed history taking, correct interpretation of laboratory results, and knowledge of rare complications of human brucellosis facilitate early diagnosis and treatment of the disease.